Hubungan Pola Asuh Orang Tua Dengan Perkembangan Anak Usia Pra Sekolah (3-5) Tahun Di Taman Kanak - Kanak Baiturohman Desa Pondok Waluh Kabupaten Jember - Ernawati Anggraeni; Ririn Handayani; Melati Puspita Sari; Yuni Handayani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Children in the pre-school period need to achieve developments that include; motor, social and language skills. Early childhood education will help in achieving this development. This study aims to determine the relationship between parenting style and the development of 3-5 year old preschool children in Baiturohman Kindergarten, Pondok Waluh Village, Jember Regency. The design of this study was Correlational Analysis with a population of 40 children and parents at Baiturohmah Kindergarten, Kencong Village, Jember Regency. The sample used in this study were 40 respondents taken by the Total Sampling method, the measuring instrument in this study used a questionnaire and KPSP, Spearman rank correlation test. The results of this study are that two variables obtained a p value of 0.001 which means <0.05 which indicates that H0 is rejected and Ha is accepted, meaning that there is a relationship between parenting parents and the development of 3-5 year old preschool children in Baiturohmah Kindergarten, Pondok Waluh Village, Jember Regency . Therefore, parents need to choose the right parenting style so that the child's development is optimal.